My favorite wife = Seine Lieblingsfrau - McCarey, Leo 1898-1969; Spewack, Bella Cohen 1899-1990; Spewack, Samuel 1899-1971 (Warner Bros. Home Entertainment, 2020)
A funny thing happens to Nick on his way to his honeymoon suite. He meets his wife. No, not his bride. He meets the wife that was lost at sea seven years ago and presumed dead.
Originally released as a motion picture in 1940
Special features: Vintage Robert Benchley short "Home movies"; December 7, 1950 "Screen Director's Playhouse" radio production starring Cary Grant and Irene Dunne; theatrical trailer
Keywords: Screwball comedy; Komödie; Liebesfilm; Spielfilm; Husband and wife / Drama; Honeymoons / Drama; Bigamy / Drama; Absence and presumption of death / Drama; Absence and presumption of death; Bigamy; Honeymoons; Husband and wife; Drama; Feature films; Video recordings for the hearing impaired; Vidéos pour personnes handicapées auditives; Film; DVD-Video